Analysis of demand for managerial and teaching staff (with knowledge of the Russian language) in the economy of the United Republic of Tanzania - N. A. Nikitin (Вестник университета, 2024)
The analysis and economic evaluation of the prerequisites of demand for Russian language teachers in the education system in Tanzania show the Russian and Tanzanian interstate projects growth, which require not only political and legal, but also educational support. The activities of domestic structures (Rossotrudnichestvo, Ministry of Education of the Russian Federation, and business structures) in Tanzania create economic prerequisites for demand for the Russian language in the country’s economy. Considering the increased level of interstate relations between the two states, due to the changes in Russia’s foreign policy course, it is possible to predict increasing demand for specialists in the field of Russian language, as well as knowledge of the language as a competitive advantage in Tanzania’s labor market. As a result of the analysis of the presence or planned presence of the structures associated with Russia, it is advisable to open centers for Russian language teachers training in the administrative districts of Tanzania, such as Zanzibar, Kigoma, Pemba, Rukwa, Mbeya, Arusha, and Mwanza. In these administrative units the interaction between the two countries is carried out or is planned, which will lead to an increase in demand for specialists speaking the Russian language, whose training is carried out as part of the main professional activity by Russian language teachers from among locally trained specialists.